Pembangunan Budaya Dalam Masa Islam Awal - Muhammad Misbahuddin (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Not only does Islam teach how to strengthen the faith, but it also teaches how a development of the culture is built. This makes sense because Islam came to the Arab society that was not an empty civilization. They had already a complete and noble culture, so the preliminary faith expression of Islam was often related to certain tradition. This what so called cultural hybridization occurred mostly in the early beginning of Islam. This condition was somehow covered by political interests and/or conflicts among sahabat, even though at that time the development of the culture was continuously going on.